2014
DOI: 10.1089/ten.tea.2013.0008
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun PLGA Fibers Incorporated with Functionalized Biomolecules for Cardiac Tissue Engineering

Abstract: Structural similarity of electrospun fibers (ESFs) to the native extracellular matrix provides great potential for the application of biofunctional ESFs in tissue engineering. This study aimed to synthesize biofunctionalized poly (Llactide-co-glycolide) (PLGA) ESFs for investigating the potential for cardiac tissue engineering application. We developed a simple but novel strategy to incorporate adhesive peptides in PLGA ESFs. Two adhesive peptides derived from laminin, YIGSR, and RGD, were covalently conjugate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(69 citation statements)
references
References 43 publications
2
62
0
1
Order By: Relevance
“…12 Meanwhile, the functional molecules (eg, drugs and growth factors) and bioactive elements can also be electrospun into the composite nanofibers to achieve high bioactivity and cell affinity. [13][14][15] Nanostructured CaP materials with high biocompatibility are usually added in the polymer solution to modify the electrospun composite nanofibers. [16][17][18] For example, hydroxyapatite (HA) and anti-inflammatory drugs can be incorporated into polycaprolactone fibers by electrospinning, achieving sustained drug release and mineralization.…”
Section: Fu Et Almentioning
confidence: 99%
“…12 Meanwhile, the functional molecules (eg, drugs and growth factors) and bioactive elements can also be electrospun into the composite nanofibers to achieve high bioactivity and cell affinity. [13][14][15] Nanostructured CaP materials with high biocompatibility are usually added in the polymer solution to modify the electrospun composite nanofibers. [16][17][18] For example, hydroxyapatite (HA) and anti-inflammatory drugs can be incorporated into polycaprolactone fibers by electrospinning, achieving sustained drug release and mineralization.…”
Section: Fu Et Almentioning
confidence: 99%
“…Two adhesive peptides N-acetyl-GRGDSPGYG (RGD) and N-acetyl-GYIGSRGYG (YIGSR) -both deriving from laminin -were mixed with PLGA to electrospin, and compared to laminincoated PLGA scaffolds [121]. In vitro studies using rat CMs indicated that the cells cultured on the YIGSR incorporated and the laminin-coated aligned scaffolds showed physiological-like morphology, while the overall superior behavior corresponded to the YIGSR-PLGA.…”
Section: Co-electrospinning With Biological Materialsmentioning
confidence: 99%
“…Fibronectin is the most widely used biological substance for cardiac cells and has been coated on chitosan [68], PCL [153] [84], PLA [154] and PU [99]. Collagen type-I was also used on P(L-D,L)LA [111] and laminin on PLGA [121]. In all cases, the cells show improved attachment, proliferation, and viability, while in some cases the desired shape of CMs is achieved.…”
Section: Co-electrospinning With Conductive Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of electrospun fibres for the support of cardiac cells has an advantage due to similarity to extracellular matrix morphology, as well as the ability to tailor fibres in dimension, composition, and functionality. Different types of fibre materials have been used for stem cell graft materials, such as nano-and micro-sized fibres with different polymer compositions [5] and bio-functionalised fibres [6]. The 3-dimensional morphology provided by the fibres makes for a good basis for a cardiac patch.…”
Section: Introductionmentioning
confidence: 99%